Peningkatan Pengetahuan Masyarakat Samarinda tentang Penyakit Artritis dan Pemeriksaan Kadar Asam Urat - Rizki Nur Azmi; Sinta Ratna Dewi; Munawarah Munawarah; Widya Rahmah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Changes will occur in the human body with increasing age. Body changes arise from early life to old age in all organs and tissues. This condition can also be seen in the joint system associated with arthritis. The introduction of disease and arthritis treatment through extension methods needs to be done to the public to raise awareness of maintaining joint health. People who participate in this awareness-raising program are given pre and posttest related to the cause of arthritis, arthritis treatment, and how to take them appropriately to reduce the side effects of the drugs that can occur. Based on the analysis of the scores from the test, it was found that there was a significant increase in public knowledge before and after the program. The community also checks uric acid levels as an initial screening for gout signs, which is one of the most common arthritis in the community. Thus, the public has a better understanding of arthritis and joint health conditions based on examining uric acid levels.